2022
DOI: 10.1172/jci148550
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development of metabolic inhibitors for oncology

Abstract: Metabolic inhibitors have been used in oncology for decades, dating back to antimetabolites developed in the 1940s. In the past 25 years, there has been increased recognition of metabolic derangements in tumor cells leading to a resurgence of interest in targeting metabolism. More recently there has been recognition that drugs targeting tumor metabolism also affect the often acidic, hypoxic, immunosuppressive tumor microenvironment (TME) and non-tumor cell populations within it, including immune cells. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 143 publications
1
46
0
Order By: Relevance
“…Only a few metabolism-based drugs for cancer have been successfully developed, and some of them are currently being tested in clinical trials. Detailed descriptions about the currently available pharmacological compounds acting on metabolism together with the up-to-date clinical trials on tumors have been recently reviewed elsewhere ( Lemberg et al, 2022 ; Stine et al, 2022 ). In this work, we have performed an unprecedented review of metabolism-related features of MB, detailing MB subgroup-specific metabolic alterations ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Only a few metabolism-based drugs for cancer have been successfully developed, and some of them are currently being tested in clinical trials. Detailed descriptions about the currently available pharmacological compounds acting on metabolism together with the up-to-date clinical trials on tumors have been recently reviewed elsewhere ( Lemberg et al, 2022 ; Stine et al, 2022 ). In this work, we have performed an unprecedented review of metabolism-related features of MB, detailing MB subgroup-specific metabolic alterations ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinic, the most advanced FAS inhibitor reported to date is TVB-2640. Combined to taxane in advanced cancers, it shows promising safety profile in first-in-human study, therefore, a phase II trial is ongoing [ 134 ]. Finally, in sorafenib-resistant HCC tumors, disruption of over-activated monounsaturated FA synthesis with SCD1 inhibitor (i.e., SSI-4) enhances sorafenib-induced tumor regression via an activation of ER-stress response [ 135 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that metabolic reprogramming impacts oncogenesis and the TME ( 32 , 33 ). Metabolic gene changes and their clinical impacts have been reported in multiple cancer types, indicating that altered metabolism-related genes may serve as promising therapeutic targets in cancer ( 16 , 34 ).…”
Section: Discussionmentioning
confidence: 99%